Laparoscopic management of adnexal masses in adolescent females: a multidisciplinary approach - Woo, Y.L.; MacDougall, J.; Latimer, J.; Crawford, R. (Springer Verlag (Germany), 2005)
Laparoscopic surgery could be considered the gold standard in managing adnexal masses. The advantages of laparoscopic surgery have been proven in the adult population, and thus its use has been promoted for treating children and adolescents. However, although adolescent females should not be treated like children, their management differs from that of adults. We present three cases to illustrate how three adolescent girls had their adnexal masses dealt with laparoscopically. We recommend that hospitals consider a combined approach in the management of large adnexal masses in adolescents by utilising the expertise of the adolescent gynaecologist, gynaecology oncologist, and minimal access surgeon. In certain centres, a particular gynaecologist may possess all the skills required.